The Startup Owner's Manual - Steve Blank, Bob Dorf (K & S Ranch, 2012)
The Startup Owner's Manual is what it says: a comprehensive, step-by-step guide to getting startup right. It walks entrepreneurs through the Customer Development process that gets them out of the building, where customers live, to develop winning products customers will buy